The Effects of Entrepreneurship Education and Family Environment on Entrepreneurial Attitudes with Motivation as Intervening Variables to Management Field at University X - R. , Achmad Drajat Aji Sujai; Susanti, Neneng; Rahmayanti, Rima (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the effect of entrepreneurship education and family environment on entrepreneurship through motivation. The type of research method used is an explanatory survey. The population in the study was 711; using a simple random sampling technique, we obtained as many as 260 samples. Analysis of statistical data used was the test of validity, reliability, classical assumption test, and path analysis. Based on the results of data processing, entrepreneurship education (X1) and family environment (X2) have a joint effect on entrepreneurial attitudes (Y). Furthermore, entrepreneurship education (X1), family environment (X2), and motivation (Z) together influence the attitude of entrepreneurship (Y) so that the model used in this study is fit or feasible. Entrepreneurship education and family environment have a positive and significant effect on the motivation of FEB University X Management study students partially. Likewise, entrepreneurship education, family environment, and motivation have a positive and significant effect on the attitude of entrepreneurship students of the FEB University X Management study program, partially. The results of path analysis show that entrepreneurship education has a direct influence on the attitude of entrepreneurship and indirectly also has an influence on motivation as an intervening variable. This means that motivation mediates entrepreneurship education. Then the family environment has a direct and indirect influence on entrepreneurial attitude, with motivation as an intervening variable.